The Determinants and Impact of Key Audit Matters Disclosure in the Auditor’s Report - Hidaya Al Lawati; Khaled Hussainey (International Journal of Financial Studies, 2022)
We investigate the determinants of key audit matters (KAMs) in the auditor’s report. In particular, we examine the impact of overlapped audit committee (AC) directors on the quantity of KAMs disclosure. We also examine the consequences of KAMs disclosure. We test to see if the quantity of KAMs disclosure affects audit quality. Oman was among the early adopters of KAMs disclosure requirement. We, therefore, use the content analysis approach to count the number of KAMs disclosed in auditor reports of financial firms listed on the Muscat Stock Market for the period of 2014 to 2019. We use regression models to test our hypotheses. Overlapped audit committee directors are measured as the ratio of AC members who also serve on other committees within the same firm. We use audit fees as a proxy for audit quality. We find that overlapped AC membership positively affects KAMs disclosure due to the knowledge spillover that results from serving on multiple committees. We also find that KAMs disclosure positively affects the quality of external auditing. We make an important and novel contribution to the literature on financial reporting, auditing and corporate governance. We add to the literature by providing the first empirical evidence of the impact of overlapped AC members on KAMs disclosure and the impact of KAMs on the quality of external auditing. The findings provide important policy implications to exceedingly appoint overlapped members on AC to enhance the level of KAMs disclosure, which leads to an improvement in audit quality.